2021
DOI: 10.1016/j.eats.2021.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Proximal Trochlear Dysplasia in the Setting of Patellar Instability: An Arthroscopic Technique

Abstract: Patellar instability is a complex disorder with multiple etiologies, and treatment must be individualized to the unique pathoanatomy of each patient. Medial patellofemoral ligament reconstruction is one of the most commonly performed procedures for the treatment of patellar instability. Patients with a symptomatic supratrochlear spur, defined by the presence of a "jumping" J sign on examination, also may benefit from an adjunctive proximal trochlear resection. Here, we describe a technique for an arthroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Trochlear dysplasia (TD) is one of the leading causes of patellar instability [ 22 ]. The most commonly used MRI parameters for TD are LTI and TFA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trochlear dysplasia (TD) is one of the leading causes of patellar instability [ 22 ]. The most commonly used MRI parameters for TD are LTI and TFA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trochlear dysplasia exists on a spectrum, resulting in an array of surgical options from minimally invasive arthroscopic bumpectomy 21 to various methods of trochleoplasty. 10 , 12 , 13 , 14 , 15 , 22 For patients with grade B and D trochlear dysplasia with a supratrochlear spur, evidence has shown that sulcus deepening trochleoplasty can improve patellofemoral stability, 17 , 23 although patients tend to also have congruent dysplasia that likewise affects the patella.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been stated that only the most proximal part of the trochlear groove, the part that represents the trochlear prominence, needs to be deepened and that a more distal deepening might be pointless and unwanted. 40 Many MRI measurements have been used to investigate TD. 30 We chose the measurements in the present study based on several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been stated that only the most proximal part of the trochlear groove, the part that represents the trochlear prominence, needs to be deepened and that a more distal deepening might be pointless and unwanted. 40…”
Section: Discussionmentioning
confidence: 99%